2020
DOI: 10.1093/pubmed/fdaa119
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining different death rates because of the COVID-19 outbreak among countries

Abstract: Background During the coronavirus disease 2019 (COVID-19) pandemic, all European countries were hit, but mortality rates were heterogenous. The aim of the current paper was to identify factors responsible for this heterogeneity. Methods Data concerning 40 countries were gathered, concerning demographics, vulnerability factors and characteristics of the national response. These variables were tested against the rate of deaths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 8 publications
0
28
0
1
Order By: Relevance
“…The ecological study including time to implementation of restriction found that this could be the most important factor. 21 However, this explains only 44% of the model, while our model explains 67% of the variability. This number was verging to the results of important study, which used individual data from nine countries showing that the age distribution of the population explains 66% of the variation across countries.…”
Section: Discussionmentioning
confidence: 58%
“…The ecological study including time to implementation of restriction found that this could be the most important factor. 21 However, this explains only 44% of the model, while our model explains 67% of the variability. This number was verging to the results of important study, which used individual data from nine countries showing that the age distribution of the population explains 66% of the variation across countries.…”
Section: Discussionmentioning
confidence: 58%
“…Zhang et al 20 analysed another relatively long study period until August, and several authors performed an analysis until July 2020 21 , 22 , 23 . Some authors standardised the start and/or end of the study period in order to be able to compare the effectiveness of NPIs across units of analysis at similar stages of the epidemic 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Gini indices of social inequality and poverty rates) and differentials in mortality rates by COVID-19; the adjusted linear regression model showed that the speed for the implementation of response strategies to the outbreak was the main predictor of mortality. 32 …”
Section: Discussionmentioning
confidence: 99%